7. IMMIGRATION SERVICE AND POLICY EVALUATIONBASED ON PUBLIC SENTIMENT:A SYSTEMATIC LITERATURE REVIEW - Al Raya Achmad Abimanyu; Nur Priyanto; Suroso; Anwar Hendro; Muchammad Furqon; Tutidikatama; Kurniawan (Staf Komunikasi dan Elektronika, TNI Angkatan Udara, 2026)
This study aims to map research trends regarding sentiment analysis and publicopinion within the immigration ecosystem. A Systematic Literature Review (SLR) methodologywas employed, adhering to the PRISMA 2020 protocol guidelines. Digital transformation throughthe implementation of Electronic Government (E-Government) has brought about fundamentalchanges in immigration administration and services. Amidst this modernization, public opinionand sentiment captured on digital platforms serve as crucial indicators for evaluating servicequality and the effectiveness of state regulations. Following processes of searching, screening,and eligibility assessment, 19 key studies published within the last five years were selected forsynthesis. Data extraction results indicate that the application of sentiment analysis in theimmigration sector can be classified into four primary dimensions: (1) evaluation of publicservice innovations and E-Government, (2) law enforcement and border security, (3) socialdynamics and international humanitarian issues, and (4) socio-economic and tourism impacts.The study concludes that public sentiment-based evaluation serves not only to measure theperformance of digital applications but also acts as an objective instrument for the government.This is essential for reconstructing adaptive immigration policies that balance serviceconvenience (prosperity approach) with the preservation of state sovereignty (securityapproach).